2015
DOI: 10.4103/0300-1652.170390
|View full text |Cite
|
Sign up to set email alerts
|

Role of transvaginal ultrasonography in diagnosing endometrial hyperplasia in pre- and post-menopause women

Abstract: Background:Abnormal uterine bleeding (AUB) is the most common presenting symptom of endometrial hyperplasia (EH). Transvaginal ultrasonography (TVS) is a diagnostic tool in the evaluation of AUB and EH with various sensitivity and specificity. However, the exact accuracy of TVS in diagnosing EH had not been evaluated. In this study, we aim to evaluate the accuracy of TVS in detecting EH.Materials and Methods:In this retrospective study, 120 women (mean age of 48.64 ± 6.74 years) with AUB with suspicious/or pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In our study, pelvic scans showed no features suggestive of malignant transformation in any women in the group, which was confirmed by histology. The exact accuracy of TVUS in diagnose of endometrial hyperplasia is not known, and the reported sensitivity varies largely between 59.7 and 100% [26,27]. Many studies generally define an endometrial thickness lower than 5.0 mm as the normal cut-off value in postmenopausal women, as endometrial thickness of 3.0-4.0 mm in postmenopausal women reduces the chance of endometrial cancer to less than 1% [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, pelvic scans showed no features suggestive of malignant transformation in any women in the group, which was confirmed by histology. The exact accuracy of TVUS in diagnose of endometrial hyperplasia is not known, and the reported sensitivity varies largely between 59.7 and 100% [26,27]. Many studies generally define an endometrial thickness lower than 5.0 mm as the normal cut-off value in postmenopausal women, as endometrial thickness of 3.0-4.0 mm in postmenopausal women reduces the chance of endometrial cancer to less than 1% [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…19 The accuracy, sensitivity, specificity, PPV, and NPV were 88.25%, 90.7%, 84%, 97.7%, and 84% in premenopausal women in AUB patients specially in endometrial hyperplasia in their study. Aslam et al reported sensitivity and specificity of TVS 81.3%, 73.6% respectively.…”
Section: Abnormal Endometrial Finding On Tvsmentioning
confidence: 99%
“…14,15 In present study the sensitivity, specificity, PPV, NPV for diagnosis of endometrial hyperplasia on TVS was 81.81, 94.43%, 90%, 95% which correlate with Shokouhi B. 16 The accuracy, sensitivity, specificity, PPV, and NPV were 88.25%, 90.7%, 84%, 97.7%, and 84% in premenopausal women in AUB patient specially in endometrial hyperplasia. Aslam reported sensitivity and specificity 81.3%, 73.6% respectively.…”
mentioning
confidence: 75%